Pengaruh Kualitas Pelayanan dan Persepsi Harga terhadap Kepuasan Konsumen pada PT. JNE Cabang Koja Jakarta Utara - Izzah, Nidaul (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2022)
This study aims to determine the effect of service quality and price perception on consumer satisfaction at PT. JNE Branch Koja North Jakarta. The research method used is a quantitative method. Data collection techniques used in this study were questionnaires and literature. The population in this study was 2,398 consumers in April 2021. The sampling technique in this study was non-probability sampling with the accidental sampling method and using the Slovin formula from Sugiyono to collect 100 respondents. The population found using the 90% confidence level or error (e) = 10% (0.1). Analysis of the data used is multiple linear regression analysis using IBM Statistics SPSS version 25 software. The results of the study indicate that service quality has an influence on consumer goals at PT. JNE Branch Koja North Jakarta by 60.7%. Price Perception has an influence on consumers at PT. JNE Branch Koja, North Jakarta by 63.5%. Service Quality and Price Perception have a significant effect on consumer goals at PT. JNE Branch Koja, North Jakarta. Service Quality and Price Perception affect consumer variables at PT. JNE Branch Koja North Jakarta simultaneously with a value of 0.699 or 69.9% of which 30.1% is explained by other factors not included in this study.Keywords: Service Quality, Price Perception, Consumer Satisfaction